Sustainable Development of Enterprises in Conditions of Smart Ecology: Analysis of The Main Problems and Development of Ways to Solve Them, Based on Artificial Intelligence Methods and Innovative Technologies - Skiter, Natalia N.; Rogachev, Aleksey F.; Ketko, Nataliya V.; Simonov, Aleksey B.; Tarasova, Irina A. (Frontiers in Environmental Science, 2022)
Relevance: Currently, the sustainability and profitability of any company is directly related to its interaction with the environment. In the 20th century it was believed that stable development is impossible, if the company focuses its production on the preservation and protection of the environment. Since the second half of the 20th century, ideas have been increasingly heard that sustainable economic development cannot be achieved at the expense of the predatory depletion of natural resources. The environmental agenda plays an important role in the ESG principles, largely formulated by UN Secretary-General Kofi Annan, reflected in Sustainable Development Goals 12–15, reflected in Resolution 70/1 - Transforming our world: the 2030 Agenda for Sustainable Development. Companies such as Tesla Motors, called “green giants”, have proven by their experience and development dynamics that in today’s environment a business that does not have a negative impact on the environment can be profitable and successful. Thus, modern trends in the development of the world economy determine the relevance of the present study, aimed at studying the new conditions of economic activity by enterprises - the conditions of smart ecology and development of recommendations for the effective transformation of enterprises under these conditions. The purpose of this study is to analyze and identify the main problems of sustainable development of enterprises in terms of preservation and protection of the environment - “smart ecology”, and based on the formulated problems the authors have developed ways to overcome them. The subject of the study are managerial and other relationships arising during the implementation of innovative Smart projects by enterprises. Methods: In the process of analyzing the problems and developing ways to overcome them and the transition of enterprises to the conditions of smart ecology, the authors used methods of system analysis, methods of statistical analysis, methods of artificial intelligence. Results: The conducted analysis shows that in modern conditions of development of innovative technologies in Russia there is no unified approach to the process of effective management of breakthrough development projects. The analysis proposed the concept of SMART ecology and showed its importance for understanding the processes taking place in the modern world. Factors influencing the effectiveness of the implementation of innovative smart ecology projects have been identified. Methods that can be used during the implementation of these projects were proposed.